THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON STOCK PRICE VOLATILITY: THE MODERATING ROLE OF TAX PAYMENT AND CEO POWER - Oktavia, Anis; Istiqomah, Dyah Febriantina (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
This study analyzes the influence of Corporate Social Responsibility (CSR) on stock price volatility by considering the moderating effect of tax payments and CEO power. The implementation of good CSR practices helps companies to maintain stock price fluctuations. The smaller the movement or fluctuation of stock prices, the lower the level of risk due to stock uncertainty. This study was conducted using a quantitative approach. The unit of analysis is manufacturing sector companies listed on the Indonesia Stock Exchange, consisting of 107 sample companies selected through a purposive sampling method with an observation period of three years from 2021 to 2023. Data analysis was performed using moderation regression and Eviews13. The results indicate that CSR practices affect stock price volatility. In addition, it is known that the role of tax payments can moderate the effect of CSR on stock price volatility. However, CEO power did not moderate the relationship between CSR and stock price volatility. This study supports the development of manufacturing companies implementing CSR practices to maintain stock price volatility. Good CSR practices can be used from an investor perspective to assess the risk of the company's shares.